FAKTOR-FAKTOR PENYEBAB PEREMPUAN HINDU BEKERJA PADA INDUSTRI BANTEN - Puspa, Ida Ayu Tary; Jendra, I Made Iwan Indrawan; Saitya, Ida Bagus Subrahmaniam (VYAVAHARA DUTA, 2020)
Ceremonies in Hinduism are carried out by people in their daily lives or certaindays. This gives an opportunity for Balinese women to play a role in the preparation of ceremonies as a means of offering at the ceremony. In this era of globalization because many Balinese women work in the public sector as employees, lecturers, medical staff, and others, causing them to have less time in preparing the ceremony. This gives an opportunity for Balinese women who love and pursue upakara to do so. There are those who make offerings as a home industry and some who work on a shop that prepares services based on orders. Hindu women who work in the banten industry, one of them is in the Desa Pakraman Penatih Denpasar Bali as the center of the banten industry is driven by two factors, namely the presence of internal and external factors. The internal factor is to increase family income and the desire to be independent. As for the external factors because of the opportunities and opportunities also because of the husband. These factors make Hindu women who work in the banten industry earn their own income that can be used for their needs independently and also for family needs.